2018
DOI: 10.1089/jir.2017.0084
|View full text |Cite
|
Sign up to set email alerts
|

Defective Dendritic Cell Cytotoxic Activity of High-Grade Glioma Patients' Results from the Low Expression of Membrane TNFα and Can Be CorrectedIn Vitroby Treatment with Recombinant IL-2 or Exogenic Double-Stranded DNA

Abstract: Besides initiation of tumor-specific T cell immunity, dendritic cells (DCs) are endowed with tumoricidal activity. Previously, we showed that monocyte-derived DCs of high-grade glioma patients generated in the presence of interferon alpha (IFNα) (IFN-DCs) have impaired cytotoxic activity against tumor necrosis factor alpha (TNFα)-sensitive HEp-2 tumor cells. Herein, we demonstrate that decreased transmembrane TNFα (tmTNFα) expression, but not soluble TNFα (sTNFα) production by high-grade glioma patient IFN-DCs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…We have previously shown that IFN-DCs from glioblastoma patients are characterized by decreased expression of mTNFα, compared to donor IFN-DCs [18]. Here, we show that expression of other molecules involved in DC cytotoxic activity in glioblastoma patients is preserved.…”
Section: Ifn-dcs From Glioblastoma Patients Do Not Differ From Donor mentioning
confidence: 46%
See 4 more Smart Citations
“…We have previously shown that IFN-DCs from glioblastoma patients are characterized by decreased expression of mTNFα, compared to donor IFN-DCs [18]. Here, we show that expression of other molecules involved in DC cytotoxic activity in glioblastoma patients is preserved.…”
Section: Ifn-dcs From Glioblastoma Patients Do Not Differ From Donor mentioning
confidence: 46%
“…Interestingly, the level of reduction in most cases corresponded to the intensity of rTNF-R1-mediated inhibitory effect, i.e., accounted for a fraction of the total cytotoxic potential mediated by TNFα/TNF-R1-dependent mechanism. We envisage that low mTNFα expression levels on IFN-DCs derived from glioblastoma patients reported in our previous study [18] could be a putative key factor contributing to the impairment of the cytotoxic DC activity against autologous tumor cells.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations